Accelerating innovation: Some lessons from the pandemic. Issue 2 (22nd April 2021) - Cooper, Robert G.
Abstract: The Pandemic taught us that accelerated new‐product development is more important than ever, and provided examples of firms developing breakthrough products in record time. Five approaches to accelerated development are outlined here: The first two deal with adequately resourcing new‐product projects, namely the use of focused teams; and effective portfolio management to prioritize projects and reallocate resources. Newer digital tools are outlined that speed new‐products developments. Finally, two development methods are described that move development projects faster: Lean development and Agile development. Accelerated development also has hidden costs: undertaking less innovative projects and cutting too many corners. Although important, the topic is under‐researched, and the limited research has yielded inconclusive results about acceleration's expected benefits.